Behavioural Economics Contribution to the Entrepreneurship Theory and its Application in Entrepreneurship Policies - N. P. Dobryagina (Управленческое консультирование, 2021)
Based on interdisciplinary research the paper proves that behavioural economics provides a significant contribution to the entrepreneurship theory and can increase the effect of policies focused on entrepreneurship motivation. The paper demonstrates that entrepreneurship is a phenomenon, which contradicts a number of neoclassical assumptions, while behavioural economics provides explanations of these deviations and embeds entrepreneurship into modified models. These new models take into account behavioural aspects of entrepreneur’s decision. The paper determines three main reasons of restrained effect of entrepreneurship policies, which are limited knowledge about existing entrepreneurship policies, underestimation of entrepreneurial sphere opportunities and importance of non-pecuniary factors in entrepreneurial decision, which are not taken into account in existing entrepreneurship determinants, used by policy makers. The paper suggests that behavioural economics approaches should be used in entrepreneurship policies as they help to deal with similar issues in other spheres.